2012
DOI: 10.1007/s00401-012-0969-5
|View full text |Cite
|
Sign up to set email alerts
|

Pleiotropic effects of miR-183~96~182 converge to regulate cell survival, proliferation and migration in medulloblastoma

Abstract: Medulloblastomas are the most common malignant brain tumors in children. Several large-scale genomic studies have detailed their heterogeneity, defining multiple subtypes with unique molecular profiles and clinical behavior. Increased expression of the miR-183∼96∼182 cluster of microRNAs has been noted in several subgroups, including the most clinically aggressive subgroup associated with genetic amplification of MYC. To understand the contribution of miR-183∼96∼182 to the pathogenesis of this aggressive subty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
122
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 151 publications
(127 citation statements)
references
References 59 publications
4
122
0
1
Order By: Relevance
“…Serum levels of miR-183 have been described in case/control studies where significantly lower levels of miR-183 are observed in stage IV non-small-cell lung carcinoma versus controls-making it a potential biomarker target for lung cancer [20]. In addition, a clinically aggressive medulloblastoma has been linked to the pleiotropic effects of the miR-183 cluster [21]. Conversely, miR-192 is highly represented in urine relative to serum.…”
Section: Results and Discussion (A) Exosome Isolation And Rna Recoverymentioning
confidence: 99%
“…Serum levels of miR-183 have been described in case/control studies where significantly lower levels of miR-183 are observed in stage IV non-small-cell lung carcinoma versus controls-making it a potential biomarker target for lung cancer [20]. In addition, a clinically aggressive medulloblastoma has been linked to the pleiotropic effects of the miR-183 cluster [21]. Conversely, miR-192 is highly represented in urine relative to serum.…”
Section: Results and Discussion (A) Exosome Isolation And Rna Recoverymentioning
confidence: 99%
“…The precise role of DICER1 in medulloblastoma is less clear. For example, subsets of miRNAs have been shown as either growth-inhibitory (Ferretti et al 2008;Li et al 2009;Venkataraman et al 2013;Jin et al 2014;Hemmesi et al 2015) or oncogenic (Grunder et al 2011;Weeraratne et al 2012;Li et al 2015). In particular, the miR-1792 cluster has been shown as both necessary and sufficient to initiate medulloblastoma (Zindy et al 2014), which suggests an oncogenic role for Dicer1 on the basis of miR-1792 alone.…”
Section: Discussionmentioning
confidence: 99%
“…According to our results, the overexpression of miR-183 and/or miR-96 in PC12 cells possibly downregulates genes induced by NGF stimulation necessary for neuronal differentiation. In this regard, Weeraratne et al (2012) showed reduced viability and migration in medulloblastoma cells after miR-183 and miR-96 knockdown. These cells acquired a more flattened appearance with projections indicative of neurite outgrowth, as well as presented an increased preneuronal gene expression signature (Weeraratne et al 2012).…”
Section: Mir183/96 Contribute To Pcc/pgl Tumorigenesis By Interferingmentioning
confidence: 93%